Workplace injuries and workforce trends - McKnight, Abigail; Elias, Peter; Wilson, Linda (Sudbury, 2001)
"Some jobs carry a greater risk of injury than others. If a job involves heavy manual labour then a greater risk of injury may be associated with it when compared with, say, a sedentary office job. The risk of workplace injury is clearly related to the job. However, previous research into the incidence of workplace injuries has also shown that some individuals appear to be more likely than others to suffer a workplace injury. This study is an attempt to unravel this puzzle using a statistical technique that can identify the risk of workplace injury associated with the affects of specific personal characteristics from those which relate to the nature of the job."